From Pre-Pandemic to Post-Pandemic Struggles to Meet Sustainable Development Goals - Birendra KC (Indonesian Journal of Tourism and Leisure, 2023)
The need to achieve Sustainable Development Goals (SDGs) is universal for all high-, middle-, and low-income nations, but the momentum was disrupted by COVID-19. Tourism is an important sector to address SDGs where the United Nations World Tourism Organization (UNWTO) emphasizes the positive role tourism could play toward meeting those goals. This paper is conceptually grounded within the scope of the SDGs and uses a case study approach. It uses the case of Nepal, a developing country, to demonstrate the struggles of developing nations to meet SDGs within the context of the pandemic. Based on the literature and available secondary data, similar cases are discussed to establish relevance for global contexts by reflecting how other developing nations with troubled tourism ecosystems due to the pandemic will negatively impact the movement on meeting SDGs. Further, future directions are proposed to gain momentum toward responding to the SDGs. Indeed, developing nations will struggle more than others, as the priority has been to deal with the COVID-19 impacts with limited available resources.